Pengaruh Literasi Keuangan, Framing Effect Dan Persepsi Risiko Dalam Pengambilan Keputusan Investasi Investor Muda Di Batam - Dewi Elizabeth; Mortigor Afrizal Purba (LPPM Universitas Putera Batam, 2026)
This study aims to analyze the influence of financial literacy, framing effects, and risk perception on investment decision-making. The study employed a quantitative approach with a survey method, involving respondents selected through purposive sampling. Data were collected using a closed-ended questionnaire with a five-point Likert scale and analyzed using multiple linear regression analysis using SPSS software. The results indicate that financial literacy has a positive and significant effect on investment decision-making. Framing effects and risk perceptions have also been shown to play a role in shaping investment decision-making behavior, albeit to varying degrees. These findings indicate that adequate financial understanding and the ability to manage risk perceptions and cognitive biases are important factors in making rational and measured investment decisions. Keywords: Financial Literacy; Framing Effect; Risk Perception; Investment Decisions.